Lymph Node Enlargement as a Manifestation of Systemic Venous Congestion in Patients with High VExUS Scores: A Case Series - Rizki Taufiqurrahman; Edi Darmawan; Sutan Syarief Muda Dalimunthe; Bastian Lubis; Andriamuri Primaputra Lubis; Rommy Fransiscus Nadea; Septian Adi Permana (CoinReads Media Prima, 2026)
Introduction: Fluid overload in critically ill patients increases central venous pressure (CVP) and induces systemic venous congestion, a recognized contributor to organ dysfunction. The Venous Excess Ultrasound Score (VExUS) is a bedside ultrasonographic method that grades venous congestion by integrating inferior vena cava (IVC) diameter with hepatic, portal, and renal venous Doppler patterns. Because the major lymphatic vessels drain into the central venous circulation through the thoracic duct, sustained elevation of CVP may also impede lymphatic outflow and cause reactive enlargement of regional lymph nodes. To describe supraclavicular lymph node enlargement as a clinical manifestation of systemic venous congestion in critically ill patients with high VExUS scores. Methods: This case series included five mechanically ventilated patients with respiratory failure and fluid overload admitted to the intensive care unit of H. Adam Malik General Hospital, Medan. Bedside ultrasonography assessed the IVC diameter and hepatic, portal, and renal venous Doppler to determine the VExUS grade, together with the evaluation of the subclavian vein and supraclavicular lymph nodes. Results: The five patients (aged 57–77 years) had a mean IVC diameter of 2.14 ± 0.21 cm. Four patients had a VExUS grade of 3, and one had a grade of 2. All patients demonstrated supraclavicular lymph node enlargement (10.3–17.6 mm), with larger nodes tending to occur in patients with higher VExUS grades. Conclusion: Supraclavicular lymph node enlargement may represent a reactive manifestation of systemic venous congestion in critically ill patients with high VExUS scores and could serve as an adjunctive parameter for assessing fluid overload in the intensive care unit setting.